Experimental Investigation and Analysis of Abrasive Water-Jet Machining Process - Sreekesh, K.; Govindan, P. (Asian Review of Mechanical Engineering, 2013)
The abrasive water-jet machining is an unconventional and eco-friendly technology used for industrial applications. This paper presents a comprehensive experimental investigation of the process, based on the material removal mechanism. The quality of surfaces machined using the process is investigated in detail. The results have indicated that surface roughness values (Ra in μm) vary between 3.5 and 5.5. The flow of abrasives, their speed and size influence quality of the machined surfaces. As the abrasive flow increases, the surface finish improves drastically. The optimum abrasive flow rate for obtaining the minimum surface roughness of 4.2 μm was corresponding to the maximum level of 7 g/s. This study has also indicated a possibility of applying abrasive water jet machining for fine polishing of machined surfaces, thereby validating the earlier investigations.